Stability and variability in the acquisition of six motor mile-stones during early infancy - Pollitt, Ernesto (2012)
The purpose of this work is to show, through evidence derived from scientific studies of healthy and well-nourished infants as well as infants selected from populations with high rates of chronic infection and malnutrition, that the order in the emergence of motor milestones is stable among these two groups. On the other hand, among the children at risk, the variance in the age of emergence of the same milestones was wider than that among the healthy and well-nourished children. The similarities between groups suggest that genetic factors explain the stability of order of emergence of the milestones, while social and cultural factors may explain the differences between groups in the variance in the age of acquisition. The information has theoretical and applied value in the evaluation of motor development in order to identify the determinants of this area of development.